LEGAL STANDING WARGA NEGARA INDONESIA DALAM PEMBUBARAN PARTAI POLITIK PERSPEKTIF HAM ISLAM - Anindita Krisma Apriliyanti (JIL : Journal of Indonesian Law, 2022)
Legal Standing The dissolution of political parties in Indonesia has never been given to Indonesian citizens. Legal Standing has always been given to the government. This affirmation is contained in Article 68 of the Constitutional Court Law and also confirmed in the Constitutional Court Decision No. 53/PUU-IX/2011 that the phrase “Government” in the dissolution of a political parties is the President. This makes citizens feel that the Government has monopolized legal standing because citizens did not have the same legal standing as the Government. This research aims to discuss the legal standing of citizens in the dissolution of political parties using an Islamic human rights perspective. The research method used is qualitative research using a normative juridical approach, namely conducting research using literature on the reality of the legal standing of disbanding political parties in Indonesia using an Islamic human rights perspective. From the results of this research, it is stated that (1) Legal standing in the dissolution of political parties in Indonesia is in accordance with Article 68 of the Constitutional Court Law that the applicant for the dissolution of political parties is the Government. (2) Based on the analysis of the legal standing of citizens in the dissolution of political parties according to the perspective of human rights in Islam, the legal standing that is only given to the government is not in line with human rights in Islam on, a) the principle of justice. b) Not in accordance with the principle of equality. and c) Not in accordance with the principle of freedom of expression.